2020
DOI: 10.3390/en14010003
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Measures for Dealing with District Heating Load Variations—A Systematic Review

Abstract: The highly varying character of district heating (DH) demand results in low capacity utilization of the DH plants, as well as increased use of fossil fuels during peak demand. The aim of this study is to present an overview and a comprehensive classification of measures intended to manage these load variations. A systematic literature review was conducted based on previously defined search strings as well as inclusion and exclusion criteria. Two scientific databases were used as data sources. Based on 96 detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 128 publications
(265 reference statements)
0
3
0
Order By: Relevance
“…This result shows that exploiting the thermal flexibility of the controlled buildings not only increases the offered electrical reserves, but can also decrease the need for peak power. This observation is also interesting for the problem of thermal reserves in district heating systems supplied by volatile renewable sources [32,69] .…”
Section: Resultsmentioning
confidence: 85%
“…This result shows that exploiting the thermal flexibility of the controlled buildings not only increases the offered electrical reserves, but can also decrease the need for peak power. This observation is also interesting for the problem of thermal reserves in district heating systems supplied by volatile renewable sources [32,69] .…”
Section: Resultsmentioning
confidence: 85%
“…In the analyzed heating plant, no information on daily variation is available. However, the authors [48][49][50] have noticed this issue in existing heating plants. In [49], the authors found that during the year, the mean daily variation in heat load is 12%.…”
Section: District Heating Parametersmentioning
confidence: 99%
“…The highest variation reached 30%, yet it was a single extreme value. Thermal storage can be used to eliminate this problem [48,50]. In the case of the proposed modernization, the variation can be compensated by the heat pumps.…”
Section: District Heating Parametersmentioning
confidence: 99%